2018
DOI: 10.2337/db18-112-lb
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Continuing Sitagliptin when Initiating Insulin Therapy in Subjects with Type 2 Diabetes Mellitus

Abstract: DPP-4 inhibitors (DPP-4is) are often discontinued with initiation of insulin therapy but the impact of this discontinuation on efficacy and hypoglycemia has not been studied. In this double-blind trial the safety and efficacy of initiating insulin while continuing sitagliptin (SITA) was evaluated. Eligible patients had inadequately controlled T2DM on metformin (MET, ≥ 1500 mg/day) in dual or triple combination therapy with a DPP-4i and/or sulfonylurea. Those on MET + SITA (100 mg/day) directly entered the tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Navíc u křehkých, zčásti nebo zcela ne soběstačných diabetiků, je to jednoduché, v praxi dobře realizovatelné léčebné schéma, které zajistí cílovou kom penzaci diabetu (zaměřenou v tomto období zejména na potlačení akutních symptomů) i u této skupiny dia betiků. To potvrzují i závěry 30týdenní randomizované studie CompoSIT I [17], kam byli zařazeni diabetici 2. typu s průměrným věkem 58,6 let, u kterých bylo nutné inten zifikovat antidiabetickou léčbu (dosud užívali metformin a sitagliptin). Při kombinaci s bazálním analogem glargin dosáhli pacienti většího poklesu HbA 1c bez zvýšení rizika hypoglykemie.…”
Section: Klinicky Vhodné Léčebné Postupy U Starších Diabetikůunclassified
“…Navíc u křehkých, zčásti nebo zcela ne soběstačných diabetiků, je to jednoduché, v praxi dobře realizovatelné léčebné schéma, které zajistí cílovou kom penzaci diabetu (zaměřenou v tomto období zejména na potlačení akutních symptomů) i u této skupiny dia betiků. To potvrzují i závěry 30týdenní randomizované studie CompoSIT I [17], kam byli zařazeni diabetici 2. typu s průměrným věkem 58,6 let, u kterých bylo nutné inten zifikovat antidiabetickou léčbu (dosud užívali metformin a sitagliptin). Při kombinaci s bazálním analogem glargin dosáhli pacienti většího poklesu HbA 1c bez zvýšení rizika hypoglykemie.…”
Section: Klinicky Vhodné Léčebné Postupy U Starších Diabetikůunclassified
“…Although limited real‐world evidence exists at this stage, trial results suggest that this type of combination therapy may be an appropriate pre‐insulin intensification option. Additional recent evidence has suggested that remaining on sitagliptin when initiating insulin provides clinical benefit …”
Section: Introductionmentioning
confidence: 99%
“…Additional recent evidence has suggested that remaining on sitagliptin when initiating insulin provides clinical benefit. 19 Although clinical trials have established the clinical benefits of sitagliptin plus SGLT2 inhibitors, and thereafter sitagliptin plus insulin, the economic impact of this treatment pathway is still unknown for healthcare systems and payers. Therefore, this study sought to evaluate the long-term cost-effectiveness of intensification with SGLT2 inhibitors compared with intensification with NPH insulin while continuing sitagliptin therapy in a UK population with T2D not at goal on metformin and sitagliptin.…”
mentioning
confidence: 99%